RETRACTED: The Effect of Work Motivation, Work Ability, and Work Discipline on The Performance of Employees of PT. The Nielsen Company Indonesia - Dea Sagita; Ahmad Cik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This research is the result of research on the effect of work motivation, work ability, and work discipline on employee performance at PT. The Nielsen Company Indonesia The research method used is the quantitative method. The results of this study used primary data in the form of a questionnaire to 100 respondents. The results of the study stated that there was a positive and significant influence between the variables of work motivation, work ability, and work discipline on the performance of employees at PT. The Nielsen Company Indonesia.